Hand Arm Vibration Syndrome Complaints among Casting Workers at a Construction Project in Indonesia - Sifa Nur Aeni; Fandita Tonyka Maharani; Azizah Musliha Fitri; Ulya Qaulan Karima (Jurnal Ergonomi dan K3, 2022)
Casting workers are at risk of experiencing HAVS complaints because in the work process required to use tools that are designed with high acceleration so that it can transmit vibrations in the hands and arms of workers during the work process takes place. This study aimed to determine the relationship of daily vibration exposure, age, duration of works, time of exposure, PPE usage, and socialization about vibration with HAVS complaints. This research uses quantitative analytic research with a cross-sectional design. The data were analyzed in univariate and bivariate ways using Chi Square Test and Independent T- test. The vibration was measured using calibrated vibration meters. The questionnaire was used for the workers. This study sample was 50 workers in the lower casting section who used Concrete Vibrators while working on Project X. The results showed that 58% of respondents had HAVS complaints. The results of the Chi-Square bivariate analysis showed a significant relationship between age (POR = 8.08; 95% CI = 2.13-30.57), daily intensity of vibration exposure (POR = 4.75; 95% CI = 1, 41-16.65), duration of exposure (POR = 5.23; 95% CI = 1.41-19.43), and use of PPE (POR = 7.80; 95% CI = 2.14-28.78 ) with HAVS Complaints. Independent T-test results showed a difference in the average daily intensity of exposure between groups with HAVS complaints of 77.42 (SD = 18.54) m/s2 and those without HAVS complaints 64.93 (SD = 15.35) m/s2. Therefore, it is advisable for workers always to use PPE, especially anti-vibration gloves, and to the management, it is advisable to install a damping device on a concrete vibrator and set the work times of workers and provide information about vibration to workers.